The Influence of Profitability, Liquidity, Solvency on Share Banking Sector Stock Price - Jefri Gunawan; Kevien Alfredo; Anastasia Sri Mendari; Binto Sartiko (Prodi Manajemen Universitas Pamulang, 2023)
The capital market is a place to trade financial instruments. This research was conducted with the aim of testing and analyzing the effect of the profitability, Liquidity, and solvency on the share price of the banking sector listed on the IDX for the 2018-2021 period. The sampling technique used in this study was purposive sampling which resulted in 47 companies with a total of 173 research data. Data analysis in this research used multiple linear regression models. This research resulted in the conclusions that profitability has a positive and significant effect on stock prices, while liquidity has a negative and significant effect on stock prices. The solvency variable has no effect on stock prices. For investors who want to invest in a company, they should pay attention to the profitability value in assessing a stock because profitability has the strongest influence on stock prices.